Ketelitian Geometrik dan Unjuk Kerja Mesin Bubut Retrofit PL 1000 G dengan Kendali Numerik - Setyawan, Mohammad Yunan; Budhi M. Suyitno; Susanto Sudiro (Magister Teknik Mesin Universitas Pancasila, 2025)
Development of equipment has been carried out in the form of adding NC systems to conventional lathes, namely PL 1000 G retrofit lathe machines integrated with the GSK 928 TE II control system.The reliability of CNC machines that have been developed needs to be tested in terms of accuracy and precision so that the influence of numerical control systems on the level of accuracy and precision is known.Tests carried out on PL 1000 G retrofit lathes include geometric testing of machine tools and testing of machine performance in accordance with SNI-05-1612-1989. From testing the performance of the retrofit machine using test samples for cylindrical tests, flatness test and thread test results nothing comes out of the tolerance limit. So overall the performance of PL 1000 G retrofit machines with numerical control is in accordance with the requirements of the SNI-05-1612-1989 standard.